Distribution variation of heavy metals in maricultural sediments and their enrichment, ecological risk and possible source—A case study from Zhelin bay in Southern China. Issue 1 (15th December 2016) - Wang, Yi; Wei, Yaning; Guo, Pengran; Pan, Jiachuan; Wu, Qihang; Liu, Ning
Abstract: The study characterized the enrichment, ecological risk and possible source of heavy metals (As, Cd, Cr, Cu, Hg, Ni, Pb and Zn) in sediments from a typical mariculture bay. The concentrations of the metals were analyzed in sediments collected from Zhelin bay. The distribution variation was examined during the past decade, which had an increase tendency till 2011. The enrichment factor and geoaccumulation indices suggested Pb, As, Cu and Zn were minor enrichment and unpolluted to moderately polluted, and Ni at cage mariculture area was moderately-severe enrichment and strongly polluted. This area had medium to high ecological risk, especially at the northwest coastal area of semi-closed bay, with high-medium to high ecological risk. Correlation and principal component analyses indicated that most of heavy metals, especially for As, Pb and Ni, primarily resulted from the combustion of gasoline and diesel fuel and the ship protective layer. Highlights: During the past decade, the distribution variation of heavy metals was examined. The enrichment and pollution of heavy metals in mariculture sediments were investigated by EFs and Igeo . The ecological risk of heavy metals in maricultural sediments was assessed by SQGs and RI，and presented by riskmap. As, Pb and Ni were primarily resulted from the combustion of gasoline and diesel fuel and the ship protective layer.